The Regulation and Reform of the American Banking System, 1900-1929. - White, Eugene Nelson, 1952- (Princeton legacy library., 2014)
Examining the regulation of banking in the United States between 1900 and the Great Depression, Eugene Nelson White shows how Congress and the state legislatures tried to strengthen the banking system by creating new institutions, rather than by changing nineteenth-century laws that perpetuated the unit structure of the banking industry. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback edi.